1008 Opportunity Costs in Paediatrics: the Specialist Registrar Experience. (October 2012) - Kandamany, N; O'Neill, MB
Abstract : Background and Aims: Recently, the pursuit of a career in Paediatrics has gradually suffered a decline. This observation prompted an evaluation of Specialist Paediatric Registrars' (SPR) perceptions of their training programme and its impact on them. Methods: Utilising an online questionnaire, all trainees in 2011 were surveyed through the RCPI database. Data sought included demographics, perceptions of career progression, work effectiveness, social impact of hospital-based training and potential career costs in paediatrics. Likert scoring (cuing at 1 not at all, cuing at 6 extremely), binary questions (scored as yes, no or unsure) and narrative options were used. Results: Fifty-three (71%) responses were obtained, with representation from each year of training. The mean Likert score was 3.8 for career progression, 4.6 for functional efficiency at work and 3.3 for attainment of a work-life balance. The value of log-books and end-of-year assessments showed positive skewing (Likert 5/6) in 8(15%) and 7(13%) respectively. Narrative responses indicated the most challenging aspect of training was time for academic pursuits 28(53%). Other concerns included relocation for 8(15%) and career uncertainty for 7(13%). SPRs cited exercise for 29(43.4%) and discussion for 19 (35.8%) as coping strategies. Thirty nine (73.6%) SPR's incurred personal costs in training with compromised family cited by half. Mean Likert score for cost acceptability was 2.8 and perceived preparedness for consultancy, post-training, scored 3.7. Conclusion: SPRs feel there is a need for change within their scheme and that paediatric training incurs significant opportunity costs, with ultimate career uncertainty.